Starlike and convex properties for Poisson distribution series - MAGESH, Nanjundan; PORWAL, Saurabh; ABIRAMI, Chinnaswamy (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
In this paper, we find the necessary and sufficient conditions, inclusion relations for Poisson distribution series belonging to the classes S ∗(α, β) and C ∗(α, β). Further, we consider an integral operator related to Poisson Distribution series. Mathematics Subject Classification (2010): 30C45.